A novel biasing mechanism for circular out-of-plane dielectric actuators based on permanent magnets. (December 2018) - Loew, P.; Rizzello, G.; Seelecke, S.
Abstract: This paper presents a novel design solution for increasing the stroke of membrane dielectric elastomer actuators (DEAs), based on a permanent magnet (PM) biasing mechanism. DEA transducers have proven to represent an effective means for the realization of large-deformation, fast, and low-power consumption mechatronic devices. In order to obtain large actuation strokes, a membrane DEA must be pre-loaded with a biasing mechanism, e.g., a spring or a mass. This paper introduces PMs as a biasing element and presents their advantages in comparison to common biasing solutions based on linear springs. A novel framework is also introduced to systematically study the whole actuator system. This framework, based on systematic force analysis, allows direct performance evaluation in case the system interacts with arbitrary load profiles, and can be effectively used to assist the actuator design. After showing the advantages of PM biased DEAs in comparison to spring biased ones, a hybrid solution based on combining PM and linear springs is also investigated. A design algorithm is then developed in order to optimize the biasing system and adapt the actuator to a given external load. Finally, the predicted system behavior is assessed by means of several experiments.